2009
DOI: 10.1364/ol.34.002927
|View full text |Cite
|
Sign up to set email alerts
|

Vortex sensing diffraction gratings

Abstract: We demonstrate a specially designed vortex sensing diffraction grating that generates multiple vortex patterns in the different diffracted orders. When this grating is illuminated with a separate vortex beam, the sign and order of the topological charge of the incident beam can be easily detected. Experimental results are shown for a variety of vortex beams including fractional values of the topological charge, and where both the diffraction grating and incident vortex illumination beam are generated by two di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
59
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(61 citation statements)
references
References 17 publications
0
59
0
2
Order By: Relevance
“…1 because intensity measurements are insensitive to the additional phase terms. In previous work, 12 we proposed a vortex sensing diffraction grating that, as we show here, is well suited for the identification of these two polarization states.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…1 because intensity measurements are insensitive to the additional phase terms. In previous work, 12 we proposed a vortex sensing diffraction grating that, as we show here, is well suited for the identification of these two polarization states.…”
mentioning
confidence: 77%
“…12,13 We first form the product V l ðϕÞG γ ðxÞ of a two-dimensional (2-D) vortex producing phase pattern V l ðϕÞ ¼ expðilϕÞ with a linear phase diffraction grating pattern G γ ðxÞ ¼ expðiγxÞ. Here x is the horizontal spatial coordinate, γ ¼ 2π∕d where d is the period of the grating and the variable l represents the topological charge of the vortex producing phase pattern.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In many investigations into the quantum nature of these beams, it is necessary to be able to detect the amount of OAM carried by the beam. There already exists a number of methods used in determining the topological charge of an optical vortex such as computer-generated holograms [14], interferometers [15,16] and SLMs [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hickmann et al [11] observed the generation of a truncated triangular optical lattice when a vortex beam passed through an equilateral triangular aperture. Moreno and Davis [12] introduced a technique to characterize the topological charge of an optical vortex through its diffraction intensity pattern after a fork-shaped grating. Guo et al [13] found that the far-field diffraction intensity pattern of an optical vortex passing through a circular annular aperture comprises some bright and dark rings, and the number of the bright rings is just equal to the topological charge value of the measured optical vortex.…”
Section: Introductionmentioning
confidence: 99%